Identifikasi Pola Bakteri di Udara Sebelum dan Sesudah Tindakan Operasi di Ruang Operasi RSU Surya Husadha Denpasar Bali - I Made Candra Wiguna; Nyoman Ngurah Adisanjaya; Ni Putu Widya Astuti (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2019)
The results of the air microbiology examination in 2018 in the operating room of Surya Husadha General Hospital, Denpasar, conducted by the environmental health laboratory of Sanglah Hospital, Denpasar, Bali, showed the presumed germ index in the operating room of Surya Husadha General Hospital Denpasar Bali not meeting the standard of Kepmenkes No.1204 / Menkes / SK / X / 2004 concerning about hospital environmental health requirements. If it is not followed properly, this can potentially cause nosocomial infections. In this study analysis data from was carried out from laboratory results based data and analyzed descriptively, regarding the identification of bacterial patterns in the air before and after surgery in the operating room.Sampling before surgery, there were 6 CFU / m3, 3 CFU / m3 and 8 CFU / m3 pathogenic bacteria, namely Staphylococcus Coagulase Negative and pseudomonas sp. Sampling after surgery was 104 CFU / m3, 104 CFU / m3 and 206 CFU / m3 pathogenic bacteria, namely Negative Staphylococcus Coagulase, Bacilus sp., Pseudomonas sp. and E. coli. Sampling before surgery has fulfilled the requirements of Kepmenkes Number 1204 / Menkes / SK / X / 2004 which is 10 CFU / m3 while the sample retrieval after the operation does not meet the Kepmenkes requirements. Keywords: Operating Theatre, Nosocomial Infection, Bacterial Pattern